2015
DOI: 10.1109/ted.2015.2439958
|View full text |Cite
|
Sign up to set email alerts
|

Cell Variability Impact on the One-Selector One-Resistor Cross-Point Array Performance

Abstract: This paper investigates the impact of cell variability on the read performance of the one-selector one-resistor (1S1R) cross-point array. A variability-aware array-sizing analysis methodology is introduced, considering three independent variability sources, namely, the data pattern randomness, the selector variability, and the resistive switching element (RSE) variability. By analyzing the impact of each variability factor separately, we show that the data pattern randomness is not an important contributor for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Among various concepts of selector device, programmable metallization cell (PMC) is one of the most promising candidates; it exhibits excellent threshold switching characteristics and simple material stacks [10,11,12]. However, the issue of variation on threshold switching voltage becomes a major problem in one-selector-one-resistor (1S1R) array integration and operation [9,13,14]. In our previous work, the SiTe based PMC selector was improved by annealing but still with large variation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among various concepts of selector device, programmable metallization cell (PMC) is one of the most promising candidates; it exhibits excellent threshold switching characteristics and simple material stacks [10,11,12]. However, the issue of variation on threshold switching voltage becomes a major problem in one-selector-one-resistor (1S1R) array integration and operation [9,13,14]. In our previous work, the SiTe based PMC selector was improved by annealing but still with large variation [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Off resistance in the BVMR determines the sneak‐path current level, which also means that its ratio to the upper‐bound resistance in the non‐MR will affect the size of scalability. For the Ta–HfO 2 non‐MR used, our estimate showed that the read margin [ 31 ] maintained a value above 10% with an array width N > 10 5 (Figure 4d and Figure S15, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…If the switching current of RRAM element is 20 uA, a selector with nonlinearity of about 4000 is required to meet all the constraints [14]. However, when it comes to the selector variability and RRAM element variability, the requirements of half-bias nonlinearity increases to 8000 [15].…”
Section: Basis Theory For Simulationmentioning
confidence: 99%